PROFESIONALISME GURU REGULER DALAM PENDIDIKAN INKLUSIF - Riani Alfianita (LPPM Universitas PGRI Adi Buana, 2021)
Regular or general education teachers need a collaboration with professionals in providing learning to children with special needs in inclusive schools. This research wants to know how to do the right assessment and learning strategies for students with special needs. This research is important to do because it specifically improves the professionalism of regular teachers in dealing with children with special needs. Based on data from the Ministry of Education and Culture in the form of dapodik for the 2015/2016 academic year, it shows that the number of junior high schools (SMP) that provide inclusive education throughout Indonesia is 3,817 schools. The method used in this research is the two main forms of policy analysis methodology according to Dunn, namely descriptive and normative.Keywords: Professionalism, Regular Teachers, Inclusive Education